Decreased Prolidase Activity in Patients with Posttraumatic Stress Disorder - (:unkn) unknown (KOREAN NEUROPSYCHIATRIC ASSOC, 2016)
Objective Many neurochemical systems have been implicated in the development of Posttraumatic Stress Disorder (PTSD). The prolidase enzyme is a cytosolic exopeptidase that detaches proline or hydroxyproline from the carboxyl terminal position of dipeptides. Prolidase has important biological effects, and to date, its role in the etiology of PTSD has not been studied. In the present study, we aimed to evaluate prolidase activity in patients with PTSD. Methods The study group consisted of patients who were diagnosed with PTSD after the earthquake that occurred in the province of Van in Turkey in 2011 (n=25); the first control group consisted of patients who experienced the earthquake but did not show PTSD symptoms (n=26) and the second control group consisted of patients who have never been exposed to a traumatic event (n=25). Prolidase activities in the patients and the control groups were determined by the ELISA method using commercial kits. Results Prolidase activity in the patient group was significantly lower when compared to the control groups. Prolidase activity was also significantly lower in the traumatized healthy subjects compared to the other healthy group (p<0.01). Conclusion The findings of the present study suggest that the decrease in prolidase activity may have neuroprotective effects in patients with PTSD.
Keywords: PTSD; Prolidase activity; Neuroprotective; NOS INHIBITOR 1-(2-TRIFLUOROMETHYLPHENYL)-IMIDAZOLE; FORCED SWIMMING TEST; NITRIC-OXIDE; OXIDATIVE-STRESS; EARTHQUAKE SURVIVORS; EXTRACELLULAR-MATRIX; ANTIDEPRESSANT-LIKE; NATURAL DISASTER; NMDA RECEPTOR; MENTAL-HEALTH